The Effect of Economic Value Added, Market Value Added and Stock Price on Stock Return (Literature Review) - Esti Kurniatin (Dinasti International Journal of Education Management And Social Science, 2023)
The capital market has an important influence on improving the economy in Indonesia, every company who wants to increase the capital will invest in the Capital Market. The company's financial performance is the main thing that potential investors will see before deciding to invest. There are several ways to measure financial performance, one of which is by using performance on value through Economic Value Added (EVA) and Market Value Added (MVA). In addition to EVA and MVA, potential investors also pay attention to the company's stock price. The main purpose of potential investors investing is to get benefits in the form of stock returns.The purpose of this scientific article The Effect of EVA, MVA and Stock Price on Stock Return is to build a hypotheses for each variables that can be applied by future research in the Field of Financial Management Science. The writing method in the scientific article uses library research methods through Mendeley, Google Scholar, and other academic online application. The results of the scientific article are: 1) EVA affects Stock Return; 2) MVA affects Stock Return; and 3) Stock Price affects Stock Return. Stock Return